Assessment of Different Biochar and Composted Cow Dung on Soil Properties, Growth and Cob Weight of Maize - Komolafe, O.O.; Adewole, M.B.; Matthew, O.J. (Department of Agronomy and Horticulture, IPB University, 2022)
Crop production in tropical soils is constrained by low fertility. The scarcity and high prices of chemical fertilizers have added to the existing challenges. This study examined the influence of different types of biochar and cow dung compost (CDC) on soil properties, growth and cob weight of maize. A polythene pot experiment was conducted at the screen house of the Institute of Ecology, Obafemi Awolowo University, Ile-Ife, Nigeria. The experiment was laid out in a completely randomized design. Amendments used were: cow dung compost, cow dung biochar and maize cob biochar, which were applied singly at the rates of 0, 4, 8, 12, 16 t.ha-1. The production of biochar from cow dung compost and maize cobs was done using a local charcoal-fired reactor. The feedstocks were slowly pyrolyzed at 350 0C and removed after 3hrs. The treatments were replicated twice. Soils amended with CDC had the highest growth parameters compared to other amendments. In the first season, CDC had a 22% increase in height compared to MCB. CDC had a height of 72 cm while MCB had the lowest height with 56 cm. The growth rate was as follows: CDC > CDB > MCB. CDC also increased cob weights when compared to other amendments. At 4 t ha-1, CDC had 2.20 g, CDB had 0.90 g while MCB had 0.47 g. Significant differences were observed among the treatments. However, it was observed that CDB increased soil chemical properties compared to other amendments. Soil properties such as organic carbon and total nitrogen were significantly improved in soils treated with CDB. This study concluded that cow dung biochar was better suited to improve soil properties while also improving crop growth compared to other amendments.